Peran Guru dalam Mengevaluasi Hasil Belajar Siswa melalui Nilai-Nilai Sosial dan Budaya - Kaffahasana, Fi Silmi; Septina, Pradita Wahyu; Wicaksono, Priagung; Soraya, Siti Zazak; Najamudin, Najamudin (Yayasan Alpatih Harapan Semesta, 2025)
This study aims to examine the role of teachers in evaluating student learning outcomes through assessments based on social and cultural values. The research uses a library research method by analyzing various up-to-date scientific literatures, including journals, books, and relevant articles. The results show that teachers play a significant role as designers of assessment tools, facilitators of contextual learning, and reflective evaluators of students' diverse social and cultural backgrounds. Assessments that integrate values such as mutual cooperation, tolerance, and local wisdom have been proven to enhance student motivation, engagement, and character development. Therefore, assessments should encompass not only cognitive aspects but also affective and psychomotor dimensions. Despite the benefits of this approach, challenges still exist, such as limited teacher training, resources, and support from schools. Adequate training, relevant instrument development, and collaboration with the community are needed for the effective implementation of social-cultural-based assessments.